1988
DOI: 10.1111/j.1600-0714.1988.tb01899.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐lymphocyte and Langerhans cell distribution in normal and allergically induced oral mucosa in contact with nickel‐containing dental alloys

Abstract: An in vivo comparison was made between the contact allergic stomatitis‐inducing capacity of nickel, nickel‐containing dental alloys and a non‐corrosive precious metal. Fifteen patients with a positive allergic skin reaction to nickel were divided into 3 groups (A, B and C). The patients in Group A (n=4) were fitted with an intra‐oral corrosion‐resistant nickel‐chromium Alloy A; the patients of Group B (n=5) received a more corrosion prone nickel‐chromium Alloy B and in Group C (n=6) strongly corroding pure nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the lympho-epidermic system of the pathological oral mucosa, the LC are involved in two steps; 1) an increase in the number of LC before the migration of lymphocytes during the inflammatory process (40), the presence of CDI + LC during the inflammation of odontogenic cysts (41), or after allergically induced oral mucosa in contact with nickel-containing dental alloys (42), and the increase of the LC HLA-DR Ag expression concomitant with the appearance of this Ag on the subepithelial T lymphocytes in lichen planus patients (43).…”
Section: Epidermal Lc (21)mentioning
confidence: 99%
“…In the lympho-epidermic system of the pathological oral mucosa, the LC are involved in two steps; 1) an increase in the number of LC before the migration of lymphocytes during the inflammatory process (40), the presence of CDI + LC during the inflammation of odontogenic cysts (41), or after allergically induced oral mucosa in contact with nickel-containing dental alloys (42), and the increase of the LC HLA-DR Ag expression concomitant with the appearance of this Ag on the subepithelial T lymphocytes in lichen planus patients (43).…”
Section: Epidermal Lc (21)mentioning
confidence: 99%
“…(Lowey, 1993) It is estimated that 11% of all women and 20% of women between the ages of 16 and 35 years have a sensitivity to nickel.6-8 Nickel-induced contact dermatitis is a Type IV delayed hypersensitivity immune response occurring at least 24 hours after exposure. (Al-Tawil, Marcusson and Moller, 1985) (Loon et al, 1988) It has been shown that the level of nickel in saliva and serum increases significantly after the insertion of fixed orthodontic appliances. (Souza, de Souza and de Menezes, 2008) Nickel leaching from orthodontic bands, brackets, stainless steel or Ni-Ti archwires has been shown in vitro to occur within the first week and then decline thereafter.…”
Section: Introductionmentioning
confidence: 99%